Do disordered eating behaviours in girls vary by school characteristics? A UK cohort study. - Bould, Helen; De Stavola, Bianca; Lewis, Glyn; Micali, Nadia (European Child & Adolescent Psychiatry, 2018)
Previous research on eating disorders, disordered eating behaviours, and whether their prevalence varies across schools, has produced inconsistent results. Our previous work using Swedish record-linkage data found that rates of diagnosed eating disorders vary between schools, with higher proportions of girls and higher proportions of highly educated parents within a school being associated with greater numbers of diagnosed eating disorders. We aimed to extend these findings to a UK population-based sample and hypothesised that a similar association would be evident when studying disordered eating behaviours. We used data from the Avon Longitudinal Study of Parents and Children to test the hypothesis that prevalence of self- and parent-reported disordered eating behaviours (binge eating, purging, fasting, restrictive eating, and fear of weight gain), and body dissatisfaction cluster by school. We had complete data on body dissatisfaction, school attended, and other possible risk factors for 2146 girls in 263 schools at age 14 and on disordered eating behaviours for 1769 girls in 273 schools at age 16. We used multilevel logistic regression modelling to assess whether prevalence varied between and within schools, and logistic regression to investigate the association between specific school characteristics and prevalence of disordered eating behaviours and body dissatisfaction. At age 14, there was no evidence for body dissatisfaction clustering by school, or for specific school characteristics being associated with body dissatisfaction. At age 16, there was no evidence for clustering, but higher rates of disordered eating behaviours were associated with attending all-girl schools and lower levels with attending schools with higher academic results. We found no evidence for clustering of disordered eating behaviours in individual schools, possibly because of the small cluster sizes. However, we found evidence for higher levels of disordered eating behaviours in 16 years in all-girl schools, and in schools with lower academic performance.